Clinical features of acute kidney injury in single center in-patients - WEI Zhi-qiang; CAO Juan; LI Hai-tao; XU Qin; YIN Di; ZHOU Chang-ju; ZHANG Xu (Linchuang shenzangbing zazhi)
Objective To investigate the epidemiology,etiology,clinical diagnosis and treatment of acute kidney injury( AKI) in adult patients,in Taixing People’s Hospital of Jiangsu Province,to provide a basis for the prevention and treatment of AKI. Methods A cross-sectional study was conducted on AKI patients,according to the screening criteria of International society of Nephrology( ISN)-AKF " 0 by 25",admitted to this hospital from March 2013 to July 2013. Results 148 patients,including 61 cases out of hospital and 87 cases in hospital respectively,were diagnosed as having AKI( 2. 0%). The total mortality rate was 0. 3%,and the mortality rate of AKI was 13. 6%. The old patients accounted for 62. 8%. Only 3. 4%patients suffered from AKI were treated in Department of Nephrology. Prerenal fators( 60. 8%) and renal factors( 27. 0%) as the main factors caused AKI. Meanwhile,infection( 27. 7%) and drug( 37. 7%)were main renal factors. Only 38. 5% patients were diagnosed timely,54. 7% were missed,while 6. 8%were delayed. 8. 1% patients got consultation. There were only 59. 5% discharged from hospital,and40. 5% died or abandoned. After one-year follow-up,10 patients lost to follow-up and 39. 8% patients died( 41. 2%). Logistic regression analysis showed that age( OR = 5. 409,95% CI: 2. 203-39. 256),multiple organ dysfunction syndrome( MODS)( OR = 16. 352,95% CI: 5. 291-86. 256) and infection( OR =12. 354,95% CI: 3. 2651-66. 128) were risk factors for prognosis. Conclusions The incidence and mortality of AKI in inpatients are high,especially in elderly patients and those with basic diseases and given renal toxicity drugs. These patients are mainly distributed in clinical departments apart from the department of nephrology,and most of them did not receive specialist diagnosis and treatment guidance. Age,combined MODS and infection are risk factors for the death of AKI patients,and the overall prognosis is poor.